Distribution and Growth of Weeds as Influenced by Intensity of Felling in Spruce and Silver Fir Forests - Singh, R. V.; Sharma, K. C.; Gupta, K. C. (Indian Forester, 1983)
The results of a study on the distribution and growth of weeds in spruce and silver fir forests worked under selection, shelter-wood uniform and clear-cutting systems are presented. The composition and relative dominance of weeds changed with the iutensity of fellings. The density and growth of weeds was the least in selection rorests and the highest in areas worked under clear-cutting system; areas worked under shelter-wood uniform system were intermediate in this respect. Total weed biomass. In clear-cut areas was 4 and 2.4 times that in those worked under selection and shelter-wood uniform systems respectively. Most of the weeds whose growth is encouralled by heavier felllngs grow tall and luxuriant and are harmful to the regeneration of spruce and silver fir.